HUBUNGAN ANTARA INDEKS MASSA TUBUH DAN DAYA TAHAN KARDIORESPIRASI PADA ANAK STUNTING USIA SEKOLAH DASAR - Jeffry Trinando; Tri Bayu Norito; Boy Indrayana; Muhammad Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Stunting is a chronic nutritional problem that can affect children's physical development, including body composition and cardiorespiratory capacity. This study aims to analyze the relationship between body mass index (BMI) and cardiorespiratory endurance in stunted children of elementary school age. A cross-sectional study was conducted on 120 stunted children aged 6-12 years in three elementary schools. Anthropometric measurements included height, weight, and BMI calculation. Cardiorespiratory endurance was measured using a 6-minute walk test. Data were analyzed using Pearson correlation and linear regression. The average BMI of the subjects was 15.2 ± 2.1 kg/m², with 65% being categorized as underweight. The average distance covered in the 6-minute test was 420 ± 68 meters. There was a moderate positive correlation (r = 0.42; p < 0.001) between BMI and cardiorespiratory endurance.There is a significant positive relationship between BMI and cardiorespiratory endurance in stunted children, indicating the importance of nutritional interventions to improve children's physical capacity.